THE EFFECT OF GIVING VIGNA RADIATE TO PUBTER MOONS ON BREAST MILK PRODUCTION IN THE WORKING AREA OF PUSTU SEMPER BARAT II I YEAR 2023 - Sitinjak, Roland; Mustafa, Ayu Resky; Sitiyaroh, Nur (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Background: Breast milk (ASI) is expected to be given to babies from birth to 2 years of age and there are still many mothers who do not provide exclusive breastfeeding on the grounds that there is little breast milk, breast milk does not come out. One intervention that can be given to increase breast milk production is by giving postpartum mothers green bean juice regularly. Objective: to study the effect of giving vigna radiate to postpartum mothers on breast milk production in the Pustu Semper Barat III Working Area. Method: Quasy Experiment, one group pre-post design, the population in this study was all postpartum mothers in the West Semper III Pustu Working Area using total sampling with a sample size of 30 respondents, using data namely primary data with observation, analysis using the T Test -Dependent. Results: From the statistical test results of the dependent t test, it is known that there is an effect of giving vigna radiate to postpartum mothers on breast milk production in the Pustu Semper Barat III Working Area in 2023 with a value of P=0.000 < 0.005. Conclusion: it is hoped that health workers can provide additional information and socialize or provide counseling when visiting about the benefits of green beans to the community, especially breastfeeding mothers, to increase their breast milk production so that later mothers can breastfeed exclusively.